2018
DOI: 10.15406/ijawb.2018.03.00082
|View full text |Cite
|
Sign up to set email alerts
|

Studies on avian diversity of banda university of agriculture and technology campus, Banda, Uttar pradesh, India

Abstract: Citation: Singh K, Maheshwari A, Dwivedi SV. Studies on avian diversity of banda university of agriculture and technology campus, Banda, Uttar pradesh, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
5
1
Order By: Relevance
“…1). This result is similar to the findings of Mallik et al (2015) and Singh et al (2018b). Muscicapidae was the most dominant family with 10 species and the highest RDi value (8.06).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1). This result is similar to the findings of Mallik et al (2015) and Singh et al (2018b). Muscicapidae was the most dominant family with 10 species and the highest RDi value (8.06).…”
Section: Resultssupporting
confidence: 92%
“…A total of 124 bird species belonging to 101 genera, distributed among 61 families and 16 orders were recorded from the campus of Acharya Narendra Deva University of Agriculture and Technology (Table 1). The bird species recorded in the current study is higher than the bird species observed at Jawaharlal Nehru University, New Delhi (Singh et al 2017), Calicut University, Malappuram (111 species) (Jose and Zacharias 2003), OUAT, Bhubaneswar (95 species) (Mallik et al 2015) and BUAT, Banda (61 species) (Singh et al 2018b), but lower than the bird species recorded at Sabaragamuwa University, SriLanka (145 species) (Surasinghe and de Alwis 2010). Passeriformes had the highest diversity with 62 species and 26 families, followed by Pelecaniformes with 9 species and 5 families (Fig.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…The main reason is habitat destruction due to deforestation for agricultural, developmental, and other purposes, as well as random tree cutting, which has resulted in a reduction in forage and nesting places for the species. 5,6 Another factor contributing to their reduction is changes in vegetation composition, which affects the quality and quantity of food, water, and cover essential for their survival, impacting the species' distribution, variety, and abundance. 7,8 The current study aims to prepare a species checklist in the Forest Research Centre (FRC) and Forest College and Research Institute (FCRI) campus as it indicated the diversity of the species in order to conserve bird's existence.…”
Section: Introductionmentioning
confidence: 99%
“…Globally around 10,787 extant species (40 Orders, 252 Families, 2359 Genera) of birds are recorded out of which 1335 species (26 orders, 113 families, and 485 genera) are recorded from India (Praveen et al, 2020c) with Gujarat state having 574 species of birds recorded (Ganpule, 2016). Avifauna is the major component of the ecological food chain and maintains the ecological balance (Singh et al, 2018). However, in present time the avifaunal diversity seems to decrease due to destruction of their natural habitat and human interference by various means like destruction of trees and natural habitats for the commercial use of wood and land (Edison et al, 2016).…”
Section: Introductionmentioning
confidence: 99%